Explicație pas cu pas:
a) 144 : (-12) + 7 × (-2)³ + 2010 =
= 144 : (-12) + 7 × (-8) + 2010 =
= -12 + (-56) + 2010 =
= -12 - 56 + 2010 =
= -68 + 2010 = 1942
b) (-88) : (-4) - 125 : (-5)² - 380 =
= (-88) : (-4) - 125 : 25 - 380 =
= 22 - 5 - 380 = 17 - 380 = -363
c) {6 - [282 × (-1) - (44 : 11 - 18)]} - 644 =
= {6 - [282 × (-1) - (4 - 18)]} - 644 =
= {6 - [282 × (-1) - (-14)]} - 644 =
= [6 - (-282 + 14)] - 644 =
= [6 - (-268)] - 644 =
= (6 + 268) - 644 =
= 274 - 644 = -370
d) 25² : (-5)² - {42 + 3 × [6 - (3³ × 5 + 11)]} =
= 25² : (-5)² - {42 + 3 × [6 - (27 × 5 + 11)]} =
= 25² : (-5)² - {42 + 3 × [6 - (135 + 11)]} =
= 25² : (-5)² - [42 + 3 × (6 - 146)] =
= 25² : (-5)² - [42 + 3 × (-140)] =
= 25² : (-5)²- [42 + (-420)] =
= 25² : (-5)² - (42 - 420) =
= 625 : 25 - (-378) =
= 25 + 378 = 403